Optimal Sequential Futures Trading - Baesel, Jerome; Grant, Dwight (Journal of Financial and Quantitative Analysis, 1982)
Hedgers adjust their futures market positions to reflect new information. Therefore, the anticipation of new information creates future decision points and thus a multiperiod decision problem. Previous studies (see [2], [4], [5], [7], and [8]) which solved the problem of choosing optimal futures market hedges have not addressed this issue. Rather, these studies have derived optimal hedges in one-period frameworks. In general, this solution is incorrect if, during the time the hedge is in effect, new information is anticipated.